2022
DOI: 10.3389/fmed.2022.880384
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Recall Under Sedation by a Novel EEG Based Index of Attention—A Pilot Study

Abstract: OverviewRecall is an accepted consequence of sedation. But due to the very low prevalence of the more devastating awareness under anesthesia (AUA), it might be of value to assess first the efficacy of new markers for AUA by their efficacy in discovering the more prevalent recall under sedation (RUS). In this pilot study we assessed whether a novel index for attentional effort, the cognitive effort index (CEI), derived in real-time from one forehead EEG channel, could differentiate between patients with or with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…We previously reviewed the literature on this topic 27 and have also demonstrated the ability to extract an EEG marker of attention during anesthesia from prefrontal delta activity. 28 We further showed that induced asymmetric focal brain injury leads to interhemispheric dissimilarity in this activity. 29 Following these earlier studies, we developed a novel EEG marker of prefrontal symmetry of activity, which might be attention-related; this is the lateral interconnection ratio (LIR).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…We previously reviewed the literature on this topic 27 and have also demonstrated the ability to extract an EEG marker of attention during anesthesia from prefrontal delta activity. 28 We further showed that induced asymmetric focal brain injury leads to interhemispheric dissimilarity in this activity. 29 Following these earlier studies, we developed a novel EEG marker of prefrontal symmetry of activity, which might be attention-related; this is the lateral interconnection ratio (LIR).…”
mentioning
confidence: 75%
“…It seems that the answer is yes. We previously reviewed the literature on this topic 27 and have also demonstrated the ability to extract an EEG marker of attention during anesthesia from prefrontal delta activity 28 . We further showed that induced asymmetric focal brain injury leads to interhemispheric dissimilarity in this activity 29 …”
mentioning
confidence: 99%
“…This renders them less practical for ongoing real-time monitoring. More recently, algorithms have been developed to extract real-time markers of attentional processes from single channels, necessitating short measurement times, at the scale of seconds [56,57,58,59 ▪ ,60 ▪ ,61,62 ▪ ,63,64,65 ▪ ,66,67].…”
Section: The Feasibility Of Monitoring Attention In Real-time Even Un...mentioning
confidence: 99%
“…As stated above, it seems that mainly selective attention markers, which are related to the perception of external stimuli, might be clearly identifiable under effective anesthesia, while markers for the more entailing sustained attention might be reduced [24 ▪ ] (see a discussion of the differences among attention processes in [71]). Therefore, when markers for sustained attention are actually noted under anesthesia, it might indicate awareness [62 ▪ ]. Thus, the use of relevant attention-related monitoring might be applicable not only to prevention of delirium, but also as a marker for awareness under anesthesia.…”
Section: The Feasibility Of Monitoring Sustained Attention For Detect...mentioning
confidence: 99%
See 1 more Smart Citation